Terrestrial Laser Scanning for the Detection of Coastal Changes along Rauk Coasts of Gotland, Baltic Sea - Sebastian Tyszkowski; Łukasz Zbucki; Halina Kaczmarek; Filip Duszyński; Mateusz C. Strzelecki (Remote Sensing, 2023)
Clusters of sea stacks, called rauks, are unique rocky landforms characteristic of Baltic Sea coasts. These limestone stacks raise interest due to their spectacular morphology and yet unexplained origin. This study presents the results of seasonal observations (2019–2020) of rauk coast changes carried out in one of the key rauk fields on Fårö Island, Sweden. The landforms developing within three test sites were examined. At Langhammars ‘classic’ field of rauks built from homogeneous limestone (1) and a shore platform devoid of rauks, underlain clearly separate limestone slabs were explored (2); and at Gamla Hamn, the analysis covered a non-typical rauk field built of densely laminated limestone (3). We applied terrestrial laser scanning (TLS) to obtain data needed in morphometric analyses and rauk surface change monitoring. We identified and determined contemporary erosional rates and dominant processes responsible for eroding and downwearing of rauk coasts. The observed changes were strongly associated with differences in local lithological and structural conditions—from a nearly complete absence within massive limestone rauks notches, to clear signs of erosion within limestone slabs eroded by waves, almost 1 m2 in size.